Analisis Kesalahan Berbahasa Bidang Morfologi dalam Laporan Isu Hoaks Corona Virus oleh KOMINFO - Agus Tika Dwi Savira; Sarifah Firda Arindita Nafarin; Siti Nur Fa’izah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to describe the language errors in the field of morphology, especially in the affixation process and its justification in the Issue Hoax Corona Virus Report by KOMINFO. The benefit of research is to provide insight and knowledge for readers on the use of good and correct Indonesian in the context of writing. Affixation errors cannot be ignored, because at first glance the error is not visible, but it is very important considering that many readers are interested in explaining the reasons why the corona virus or covid-19 hoax issues. This approach uses descriptive qualitative research methods with data collection techniques refer to, record and take samples. The method used to analyze the data is the aggregate method. The results of this study indicate that there are still many language errors even repeatedly in the report on the issue of corona virus hoaks by KOMINFO. Errors in this study include 8 prefix errors, 0 infix errors, 18 suffix errors and 12 confix errors.This research aims to describe the language errors in the field of morphology, especially in the affixation process and its justification in the Issue Hoax Corona Virus Report by KOMINFO. This approach uses descriptive qualitative research methods with data collection techniques refer to, record and take samples. The method used to analyze the data is the aggregate method. The results of this study indicate that there are still many language errors even repeatedly in the report on the issue of corona virus hoaks by KOMINFO. Errors in this study include 8 prefix errors, 0 infix errors, 18 suffix errors and 12 confix errors.